Evaluation of Functional Outcome of Percutaneous Lateral Pinning Compared With Crossed Pinning in Supracondylar Fracture Of Humerus (Gartland Type-III) in Children (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Of the various methods available for the treatment of Gartland type III fractures percutaneous Kwire fixation either in a cross medio-lateral patternor through a lateral entry is the treatment of choice.  Purpose of the study was to evaluate the functional outcome of percutaneous lateral pinning compared with crossed pinning in supracondylar fracture of humerus (Gartland Type–III) in children.Materials and methods: This quasi-experimental study was carried out in the Department of Orthopaedic Surgery, Chittagong Medical College Hospital from July 2018 to January 2020. Thirty patients with age limit below 12 years having supracondylar fracture of Humerus (Gartland Type-III) were taken by purposive sampling technique as per set criteria and were treated either by lateral pinning or crossed pinning. Every alternate patint ws included in the same group.  Results: In this study, Out of 30 patients, 15 patients were undergone fixation with lateral pinning and15 patients were undergone fixation with cross pinning. Male 26(86.7%) were more than female 4(13.3%), left side involvement was 76.7% and right side was 23.7%. Lt. side was more as most of the patients were Rt. Dominant and was trying to protect during fall with the help of non dominant hand. In 73.43% had used 2 pin, 26.57% had used 3 pin during procedure. Mean ± SD interval from injury to procedure in the study subjects were 4.33 ± 2.496 days (Range: 1-10 days). Mean ± SD time in lateral pinning group was 31 ± 4.424 minutes and in cross pinning group was 30.07 ± 4.234 minutes. No patient had ulnar nerve injury in lateral pinning group, but 13.33% patients had ulnar nerve injury during procedure in cross pinning group. Functional outcome was 67.7% excellent and 33.3% good in lateral pinning group and 73.3% excellent and 26.7% good in cross pinning group according to Flynn Criteria. Mean ± SD change in Humerocapitellar angle in lateral pinning group was 5.47 ± 0.640 degree and in cross pinning group was 6.07± 1.223 degree. Mean ± SD change in baumann’s angle in lateral pinning group was 3.53 ±0.64 and cross pinning group was 5.00 ±1.00 degree.  Conclusion: This study showed techniques of lateral pinning and medio-lateral cross pinning are equally effective for fixation of paediatric supracondylar fracture of humerus. JCMCTA 2024 ; 35 (1) : 28-32